2019
DOI: 10.1186/s12889-018-6336-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of integrated disease surveillance and response (IDSR) core and support functions after the revitalisation of IDSR in Uganda from 2012 to 2016

Abstract: BackgroundUganda is a low income country that continues to experience disease outbreaks caused by emerging and re-emerging diseases such as cholera, meningococcal meningitis, typhoid and viral haemorrhagic fevers. The Integrated Disease Surveillance and Response (IDSR) strategy was adopted by WHO-AFRO in 1998 as a comprehensive strategy to improve disease surveillance and response in WHO Member States in Africa and was adopted in Uganda in 2000. To address persistent inconsistencies and inadequacies in the cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
84
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(93 citation statements)
references
References 21 publications
6
84
0
Order By: Relevance
“…Future research should examine the benefits of eIDSR in Sierra Leone, as establishment of eIDSR is expected to improve data timeliness, completeness, quality, and access, [4][5][6]18 but these have yet to be assessed. Additionally, costsaving opportunities should be explored, such as alternative mobile device management solutions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Future research should examine the benefits of eIDSR in Sierra Leone, as establishment of eIDSR is expected to improve data timeliness, completeness, quality, and access, [4][5][6]18 but these have yet to be assessed. Additionally, costsaving opportunities should be explored, such as alternative mobile device management solutions.…”
Section: Resultsmentioning
confidence: 99%
“…This study estimates costs to expand an established electronic system, health facility eIDSR, to a new district and is the first estimation of operational costs needed to sustain eIDSR. As use of electronic platforms to perform IDSR reporting and analysis becomes more popular, [4][5][6] understanding the costs to roll out the system is valuable to Sierra Leone and other IDSR implementers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These support functions included training, provision of case de nitions, reporting tools, and android phones might have contributed to the improvement in the reporting. Experiences shared from Uganda among participants at a focus group discussion showed that training on IDSR at the operational levels led to the improvement in the completeness and timeliness of reporting, case detection, and data analysis [23,24]. Timeliness and completeness are two critical complementary performance indicators of the IDSR strategy.…”
Section: Discussionmentioning
confidence: 99%